2001
DOI: 10.1159/000054641
|View full text |Cite
|
Sign up to set email alerts
|

Low Leptin Levels but Norma Body Mass Indices in Patients with Depression or Schizophrenia

Abstract: Appetite, food intake and weight are frequently altered in psychiatric disorders such as major depression and schizophrenia. The few studies investigating weight and the body mass index (BMI) have yielded variable results. Leptin, a fat cell-derived hormone signalling to the brain the size of the adipose tissue, plays a pivotal role in the regulation of weight and food intake. Moreover, leptin is involved in the control of other behaviors and in brain development. There is almost no information about the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
120
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 24 publications
8
120
1
3
Order By: Relevance
“…These results are consistent with the findings of Collin et al (36) who observed that ob/ob mice (leptin-deficient) exhibited significantly lower locomotor activity and increased immobility compared to their lean littermates. In addition, a clinical study performed by Kraus and colleagues (37) showed low levels of leptin in depressed patients. In contrast, we found no difference in immobility between mice treated or not with leptin.…”
Section: Discussionmentioning
confidence: 96%
“…These results are consistent with the findings of Collin et al (36) who observed that ob/ob mice (leptin-deficient) exhibited significantly lower locomotor activity and increased immobility compared to their lean littermates. In addition, a clinical study performed by Kraus and colleagues (37) showed low levels of leptin in depressed patients. In contrast, we found no difference in immobility between mice treated or not with leptin.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, other reports found that low leptin levels were associated with depression. With larger sample sizes, two research groups demonstrated that plasma leptin levels were decreased in patients with major depression independent of body mass status [21,22]. Also, lower levels of leptin in cerebrospinal fluid were found in suicide attempters with depression than those without depression [23,24].…”
Section: Human Studiesmentioning
confidence: 99%
“…The difference remained significant after adjustment for the covariates of BMI, age, medication and smoking. 56 Both IL-6 and leptin can influence bone metabolism. IL-6 and its receptor can modulate bone remodeling by regulating both osteoclast and osteoblast development and function.…”
Section: Inteleukin-6 (Il-6) and Leptinmentioning
confidence: 99%